KEANEKARAGAMAN JENIS TUMBUHAN OBAT DAN PEMANFAATANYA DI KAWASAN HUTAN LINDUNG GUNUNG SALAHUTU - Sahusilawane, John F; Bone, Iskar; Puttileihalat, Maya MS (Universitas Pattimura, 2024)
This research aims to inventory the diversity of plant species used as medicine by the people of the Mount Salahutu Protected Forest area; study the traditional knowledge of the community in the use and preservation of medicinal plants. The research method for plant data is inventory of plant types and ethnobotany to obtain plant collections, which are determined randomly (purposive random sampling). Next, the plant data obtained from interviews with the community was then ground checked. The results of the research found a diversity of types of medicinal plants at the location, 37 types of plants were recorded which were used by the local community as medicinal herbs. Plant types consist of 27 families. The Arecaceae, Euphorbiaceae, and Moraceae families are the families that have the most types of medicinal plants. The types of medicinal plants used as medicine are parts of the fruit, leaves, stems, bark and wood as well as whole plants by pounding and boiling (not using flowers).